The relationship between gambling attitudes, involvement, and problems in adolescence: Examining the moderating role of coping strategies and parenting styles - Dixon, R.; Youseff, G.; Hasking, Penelope; Yucel, M.; Jackson, A.; Dowling, N. (2016)
Introduction: Several factors are associated with an increased risk of adolescent problem gambling, including positive gambling attitudes, higher levels of gambling involvement, ineffective coping strategies and unhelpful parenting practices. It is less clear, however, how these factors interact or influence each other in the development of problem gambling behavior during adolescence. The aim of the current study was to simultaneously explore these predictors, with a particular focus on the extent to which coping skills and parenting styles may moderate the expected association between gambling involvement and gambling problems. Methods: Participants were 612 high school students. The data were analyzed using a zero-inflated Poisson (ZIP) regression model, controlling for gender. Results: Although several variables predicted the number of symptoms associated with problem gambling, none of them predicted the probability of displaying any problem gambling. Gambling involvement fully mediated the relationship between positive gambling attitudes and gambling problem severity. There was a significant relationship between gambling involvement and problems at any level of problem focused coping, reference to others and inconsistent discipline. However, adaptive coping styles employed by adolescents and consistent disciplinary practices by parents were buffers of gambling problems at low levels of adolescent gambling involvement, but failed to protect adolescents when their gambling involvement was high. Conclusions: These findings indicate that research exploring the development of gambling problems is required and imply that coping and parenting interventions may have particular utility for adolescents who are at risk of development gambling problems but who are not gambling frequently.